Internet of Things for Smart Cities Technologies, Big Data and Security - Ejaz, Waleed; Anpalagan, Alagan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book introduces the concept of smart city as the potential solution to the challenges created by urbanization. The Internet of Things (IoT) offers novel features with minimum human intervention in smart cities. This book describes different components of Internet of Things (IoT) for smart cities including sensor technologies, communication technologies, big data analytics and security.
Chapter 1.Internet of Things for Smart Cities: Overview and Key Challenges -- Chapter 2.Communication Technologies and Protocols for Internet of Things -- Chapter 3.Big Data in IoT: Processing, Storage, and Analytics -- Chapter 4.Internet of Things enabled Electric Vehicles in Smart Cities -- Chapter 5.Blockchain Technology for Security and Privacy in Internet of Things.
Keywords: Electronic circuits; Signal processing; Telecommunication; Electronic Circuits and Systems; Signal, Speech and Image Processing; Communications Engineering, Networks